Exponential protocols for cardiopulmonary exercise testing on treadmill and cycle ergometer - Jamison, J. P.; Megarry, J.; Riley, M. (European Journal of Applied Physiology, 2010)
An extended exponential exercise protocol was validated by comparing submaximal and maximal parameters with those obtained by linear protocol. Normal subjects (n = 16, 20-69 years) undertook maximal exercise tests on treadmill and cycle ergometer. The subjects had a wide range of exercise capacity, and all were accommodated by the protocol. Mean oxygen uptake ([(V)\dot]\textO 2 ) (VO2)agreed between protocols at gas exchange anaerobic threshold (?) (95% CI of difference -0.1 to +0.06 l min-1) and at peak (95% CI of difference -0.1 to +0.1 l min-1). Mean pre-q\Updelta [(V)\dot]\textO2 /\Updelta \textwork rate([(W)\dot]) Unknown control sequence '\Updelta'slope on the cycle ergometer agreed between protocols (95% CI of the difference -0.9 to +0.25 ml min-1 W-1). Post-q\Updelta [(V)\dot]\textO2 /\Updelta [(W)\dot] Unknown control sequence '\Updelta'slope was steeper than pre-?, and steeper by linear than by exponential protocol (P = 0.0001). It is concluded that the exponential protocol is valid for the measurement of submaximal and maximal exercise parameters in subjects with a wide range of exercise capacity.